Early marriage and health risks in children born: Scoping review - Rezka Zahra Humaira; Farida Kartini (Universitas Aisyah Pringsewu, 2023)
Background: Early marriage in adolescents is widely found and it results in a poor risk to the newborn infants they delivered. Yet, scoping review research concerning the health impacts on the children born was not commonly found. Most of the scoping review research merely discussed the impact of adolescents. Purpose: To determine the impacts of early marriage on children's health. Method: The literature study employed scoping review approach by adapting the PRISMA-ScR checklist and using the PEOS framework mentioning “early marriage and readiness to be a parent” “early marriage” “risk factor for early marriage on adolescent reproductive readiness” “reproductive health in children who marry early” “toddler development in early marriage”. Five databases were used in this study: Willey, Science Direct, Pubmed, Proquest, and Google Scholar. The data selection was conducted using a flowchart prism and critical appraisal tool of Joanna Briggs Institute (JBI). Result: Based on the search of 486 articles, there were ten articles relevant to the purpose of this study and hence included in scoping review. Three themes were then selected based on the mapping results considering role and health of young mothers, toddlers’ condition, environment and economy. Conclusion: Children born to adolescent mothers tend to have poor nutrition and development, such as developmental delay, anemia, and stunting. This is due to both mothers’ developing psychology and body, so they are most likely not ready to look after the children and family. Abstrak: Latar Belakang: pernikahan dini pada remaja masih banyak dilakukan dan hal ini dapat memberikan risiko buruk pada anak yang dilahirkannya nanti. Penelitian scoping review mengenai dampak kesehatan pada anak yang dilahirkan masih tidak terlalu banyak ditemukan, banyak penelitian scoping review yang ditemukan hanya membahas mengenai dampak pada remaja sendiri bukan terhadap anaknya. Tujuan: untuk mengetahui bagaimana dampak pernikahan dini pada kesehatan anak yang dilahirkan. Metode: studi literatur ini menggunakan pendekatan scoping review yang diadaptasi dengan PRISMA-ScR checklist, menggunakan framework PEO’s yaitu “early marriage and readiness to be a parent” “early marriage” “risk factor for early marriage on adolescent reproductive readiness” “reproductive health in children who marry early” “toddler development in early marriage”. Terdapat lima database yang digunakan yaitu willey, science direct, pubmed, proquest, google scholar. Kemudian dilakukan seleksi data dilakukan menggunakan prisma flowchart dan critical appraisal menggunakan Joanna Briggs Institute (JBI). Hasil: berdasarkan dari 486 artikel hasil pencarian diperoleh 10 artikel yang relevan dengan tujuan dari penelitian dan dapat dimasukkan dalam scoping review. Didapatkan 3 tema dari hasil pemetaan yaitu peran dan kesehatan ibu remaja, keadaan balita, lingkungan dan ekonomi. Simpulan: Anak yang lahir dari ibu remaja cenderung memiliki gizi serta perkembangan yang tidak baik seperti terhambatnya perkembangan anak, anemia dan stunting. Hal ini karena baik dari psikologis ibu dan tubuh ibu sedang berkembang sehingga kemungkinan besar ibu belum memiliki kesiapan diri untuk merawat anak dan keluarganya